On the coexistence pressure between the bulk and adsorbed argon on substrates of different strength – Temperature dependence of the characteristics of the adsorbate - Prasetyo, L.; Xu, H.; Fan, Chunyan; Do, D.D.; Nicholson, D. (ELSEVIER SCIENCE SA, 2019)
© 2019 Elsevier B.V. Isotherms for adsorption of gases on non-porous substrates have been recorded which cross the ordinate axis at the bulk coexistence pressure, P0 at low temperatures (usually less than the triple point temperature TTr). We have carried out simulations of argon adsorption on substrates of different strengths, to investigate the isotherms, isosteric heats and the adsorbate structures responsible for the crossing of the P/P0 = 1 axis. It is shown that there exists a coexistence pressure P0* between the thick adsorbed film and the bulk gas, and it is found to be less than the pressure of the bulk supercooled liquid, P0L. This indicates that the adsorbed film is not as disordered as the bulk liquid and is not as crystalline as the bulk solid, as confirmed by the distribution of the local order parameter Q6m. This is because the propagation effect of the planar substrate prevents the adsorbate from forming fcc structures. While the isotherms for substrates of different strength at low to moderate loadings behave differently, they overlap as the pressure approaches P0*, indicating that their thick adsorbed films have similar molecular structure. This similarity is confirmed by the trends in isosteric heat versus loading. At high enough loadings, the isosteric heat approaches λ*, which is smaller than the bulk sublimation heat for temperatures less than TTr, but greater than the heat of condensation extrapolated from those values above TTr; while for temperatures greater than the roughening temperature TR, it approaches the heat of condensation.